Pharmacokinetic Variables of Dapagliflozin/Metformin Extended-release Fixed-dose Combination in Healthy Chinese Volunteers and Regional Comparison - Zhao, Xiaoying; Ning, Rui; Hui, Andrew; Boulton, David W.; Tang, Weifeng (Clinical therapeutics, 2023)
A fixed-dose combination (FDC) product combining dapagliflozin and metformin may increase medication adherence in patients with type 2 diabetes mellitus (T2DM) by minimizing pill burden associated with co-administration of individual component (IC) formulations and, consequently, improve cost-efficiency and compliance. This study evaluated the bioequivalence of the dapagliflozin/metformin FDC product versus IC administration in healthy volunteers from a Chinese population and assessed the safety profile of the FDC product. In addition, pharmacokinetic (PK) and safety comparisons of dapagliflozin and metformin across different regions were conducted to evaluate regional differences. This single-center, open-label, parallel-cohort, randomized, 2-period, crossover study enrolled Chinese adults (aged 18–55 years). Volunteers in cohort 1 received either a single FDC tablet of dapagliflozin/metformin extended release (XR) (5/500 mg) or IC tablets (dapagliflozin [5 mg] and metformin XR [500 mg]). Volunteers in cohort 2 received a higher dosage in a similar manner (dapagliflozin [10 mg] and metformin XR [1000 mg]). Volunteers in each cohort were subsequently crossed over to receive the alternate cohort treatment. Plasma concentrations of dapagliflozin and metformin were determined, and bioequivalence analyses were performed under standard fed conditions. Eighty healthy Chinese volunteers (89.9% male; mean age, 28.7 years) were randomized into cohort 1 (n = 40) and cohort 2 (n = 39; 1 volunteer withdrew before receiving study treatment). The mean plasma concentration–time profiles of the dapagliflozin and metformin FDC and IC formulations for both doses were found to be nearly superimposable. Dapagliflozin and metformin XR FDC were bioequivalent to the IC tablets, with 90% CIs for each pairwise comparison contained within the 80% to 125% bioequivalence limits. Both the FDC and IC formulations were well tolerated, with no serious adverse events/death. PK parameters for dapagliflozin in the Chinese volunteers were slightly to moderately higher than those from studies conducted in Brazil, Russia, and the United States, and the safety profile of the dapagliflozin/metformin FDC product was consistent with that of other studies. The difference in PK parameters among the 4 regions was not clinically meaningful. The bioequivalence of the dapagliflozin/metformin FDC and IC formulations in healthy Chinese adults was established without any new safety concerns. Notably, the observed bioequivalence may be extrapolated to patients with T2DM as the PK parameters of dapagliflozin and metformin in healthy adults are similar to those reported in patients with T2DM. ClinicalTrials.gov identifier: NCT04856007.